2013
DOI: 10.1007/s11011-013-9435-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunctions in Myalgic Encephalomyelitis / chronic fatigue syndrome explained by activated immuno-inflammatory, oxidative and nitrosative stress pathways

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/cfs) is classified by the World Health Organization as a disorder of the central nervous system. ME/cfs is an neuro-immune disorder accompanied by chronic low-grade inflammation, increased levels of oxidative and nitrosative stress (O&NS), O&NS-mediated damage to fatty acids, DNA and proteins, autoimmune reactions directed against neoantigens and brain disorders. Mitochondrial dysfunctions have been found in ME/cfs, e.g. lowered ATP production, impaired ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 241 publications
3
127
0
Order By: Relevance
“…These factors are associated with PDK (22) and SIRT4 (47) in the regulation of oxidative metabolism. Such signaling pathways involve factors previously linked to ME/CFS, such as reactive oxygen species associated with signaling and mitochondrial dysfunction (48), and nitric oxide related to endothelial dysfunction, which has been demonstrated in ME/CFS (27). AMPK activates the endothelial nitric oxide synthase enzyme (eNOS) (49), and corrupted AMPK signaling may be a mechanism in endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are associated with PDK (22) and SIRT4 (47) in the regulation of oxidative metabolism. Such signaling pathways involve factors previously linked to ME/CFS, such as reactive oxygen species associated with signaling and mitochondrial dysfunction (48), and nitric oxide related to endothelial dysfunction, which has been demonstrated in ME/CFS (27). AMPK activates the endothelial nitric oxide synthase enzyme (eNOS) (49), and corrupted AMPK signaling may be a mechanism in endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Its dysfunction will lead to cell disorders of energy supply, and ultimately result in cell apoptosis or death. The decreased mitochondrial membrane potential (MMP) is an early event of apoptosis, and the disappearance of MMP is often regarded as a symbol of irreversible cell death process (Zhang et al, 2015;Morris and Maes, 2014). By flow cytometry, Guratowska et al (2010) found significantly increased apoptosis of the lymphocytes correlated highly with the COpoisoning severity, but did not depend on hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of ME/CFS do not use biological markers. Several body systems such as the muscular and nervous systems are affected in a context of neuro-immune alterations and chronic low-grade inflammation [36]. The etiology of ME/CFS is unknown, and its pathogenesis appears to be multifactorial, various stressors being repeatedly reported in the medical history of these patients, notably an intense sport practice, severe infections, and/or emotional stress [7, 8].…”
Section: Introductionmentioning
confidence: 99%